Nursing Information Flow in Long-Term Care Facilities - Wei, Quan; Courtney, Karen L. (Applied Clinical Informatics, 2018)
Objective Long-term care (LTC), residential care requiring 24-hour nursing services, plays an important role in the health care service delivery system. The purpose of this study was to identify the needed clinical information and information flow to support LTC Registered Nurses (RNs) in care collaboration and clinical decision making.Methods This descriptive qualitative study combines direct observations and semistructured interviews, conducted at Alberta's LTC facilities between May 2014 and August 2015. The constant comparative method (CCM) of joint coding was used for data analysis.Results Nine RNs from six LTC facilities participated in the study. The RN practice environment includes two essential RN information management aspects: information resources and information spaces. Ten commonly used information resources by RNs included: (1) RN-personal notes; (2) facility-specific templates/forms; (3) nursing processes/tasks; (4) paper-based resident profile; (5) daily care plans; (6) RN-notebooks; (7) medication administration records (MARs); (8) reporting software application (RAI-MDS); (9) people (care providers); and (10) references (i.e., books). Nurses used a combination of shared information spaces, such as the Nurses Station or RN-notebook, and personal information spaces, such as personal notebooks or “sticky” notes. Four essential RN information management functions were identified: collection, classification, storage, and distribution. Six sets of information were necessary to perform RN care tasks and communication, including: (1) admission, discharge, and transfer (ADT); (2) assessment; (3) care plan; (4) intervention (with two subsets: medication and care procedure); (5) report; and (6) reference. Based on the RN information management system requirements, a graphic information flow model was constructed.Conclusion This baseline study identified key components of a current LTC nursing information management system. The information flow model may assist health information technology (HIT) developers to consolidate the design of HIT solutions for LTC, and serve as a communication tool between nurses and information technology (IT) staff to refine requirements and support further LTC HIT research.
Keywords: electronic health records; nursing informatics; Canada; skilled nursing facilities